Return performance, Cointegration and short run dynamics of Islamic and non-Islamic indices: Evidence from the US and Malaysia during the subprime crisis - Mohamed Shikh Albaity; Hamdia Mudor (Atlantic Review of Economics, 2012)
This paper studies the returns difference, the long run relationship, and the short run dynamics of Islamic indices compared to non-Islamic indices in three sub periods as well as the overall period. The sub periods studied are the pre-, post and during the recent subprime crisis. The results indicate that there is no significant difference in mean returns between the Islamic indices as well as their counterparts. In terms of long run relationship or cointegration it is found that the Islamic indices were cointegrated in the pre-crisis as well as post crisis period. On the other hand the conventional indices were not cointegrated in any of the sub periods. The short run causality between the Islamic indices is a unidirectional from DJIMI towards HJ in all the sub-periods. Similarly, the conventional indices have a unidirectional causality running from DJINA towards KLCI except during the financial crisis where a bidirectional relationship exists. The result here suggests that the screening criteria of Islamic indices eliminate doubtful stocks before they fail is not accurate. In other words, if the Islamic indices screening criteria have any benefit in identifying the failing stocks they would have at least minimized the effect of the financial crisis. Therefore, investing in Islamic indices has no superiority over the conventional index in terms of performance. However, Islamic investment might have the peace of mind some investors are looking for.
Keywords: 330